Manajemen Program Akselerasi Baca Kitab Kuning melalui Metode Nubdzatul Bayan di Pondok Pesantren Darul Lugah Wal Karomah Kraksaan Probolinggo - Moh. Nurzin; Mamluatun Ni’mah; Sollah Solehudin (Attractive : Innovative Education Journal, 2024)
The aim of this research is to determine the management of the yellow book reading acceleration program using the Nubdzatul Bayan method at the Darullughah Walkaromah Kraksaan Probolinggo Islamic Boarding School. This research uses qualitative research methods with a field study approach. In collecting data, researchers used observation, interview and documentation techniques. And the analysis technique uses the Miles & Huberman model, namely by reducing data, presenting data and drawing conclusions. The results of this research show that accelerated management of yellow book reading through the Nubdzatul Bayan method can improve students' ability to read the yellow book in a faster time span.